Effects of Placing Anterior Cruciate Ligament Grafts in Vancomycin Powder Reduces Infection Rate - Muhammad Amir Sohail; Iram Saddique; Tooba Mazhar (JLUMHS, 2023)
OBJECTIVE: To determine the effects of putting Anterior Cruciate Ligament (ACL) grafts in vancomycin powder before reconstruction surgery lowers the risk of infection post-operatively. METHODOLOGY: An observational COHORT Study was conducted at Jinnah Hospital Lahore from 2017-202. Based on the use of vancomycin, all ACL reconstructions carried out between 2017-2022 at single Hospital settings were examined. This study contained a total sample of 100 subjects, all on pre-vancomycin protocol. A standard follow-up examination was conducted every two weeks (Follow-up rate was 95%). The Statistical analysis was done. The level of significance was < 0.05. RESULTS: The study revealed that out of 100 participants, 96% Males and 4% females participated with a mean age of 25.26±3.86. Of them, 42(42%) were in the age range of 18-24 years, and 58(58%) were in the age range of 25-32 years. Out of 100 Participants, 63(63%) had mild pain, and 37(37%) had moderate pain after surgery. One hundred individuals underwent ACL Graft surgery; 97(97%) had no infection, and 3(3%) had an infection after the ACL grafts were placed in Vancomycin Powder. Conclusion: Vancomycin pre-placing and vancomycin wrap dramatically lower the risk of infection after ACLR in hamstring auto grafts. According to statistical analysis, the ACL graft's previous use of vancomycin powder considerably decreased the infection rate compared to individuals for whom this procedure was not used.